A free radical scavenger edaravone suppresses systemic inflammatory responses in a rat transient focal ischemia model. (28th October 2016) - Fujiwara, Norio; Som, Angel T.; Pham, Loc-Duyen D.; Lee, Brian J.; Mandeville, Emiri T.; Lo, Eng H.; Arai, Ken
Highlights: A radical scavenger edaravone reduced infract volume and edema formation in a rat stroke model. Edaravone decreased plasma IL-1beta and MMP-9 levels under ischemic conditions. Edaravone suppressed stroke-induced upregulations of inflammatory cytokines in plasma. Abstract: A free radical scavenger edaravone is clinically used in Japan for acute stroke, and several basic researches have carefully examined the mechanisms of edaravone's protective effects. However, its actions on pro-inflammatory responses under stroke are still understudied. In this study, we subjected adult male Sprague-Dawley rats to 90-min middle cerebral artery (MCA) occlusion followed by reperfusion. Edaravone was treated twice via tail vein; after MCA occlusion and after reperfusion. As expected, edaravone-treated group showed less infarct volume and edema formation compared with control group at 24-h after an ischemic onset. Furthermore, edaravone reduced the levels of plasma interleukin (IL)-1β and matrix metalloproteinase-9 at 3-h after ischemic onset. Several molecules besides IL-1β and MMP-9 are involved in inflammatory responses under stroke conditions. Therefore, we also examined whether edaravone treatment could decrease a wide range of pro-inflammatory cytokines/chemokines by testing rat plasma samples with a rat cytokine array. MCAO rats showed elevations in plasma levels of CINC-1, Fractalkine, IL-1α, IL-1ra, IL-6, IL-10, IP-10, MIG, MIP-1α, and MIP-3α, and all these increases were reduced by edaravone treatment. These data suggest that free radical scavengers may reduce systemic inflammatory responses under acute stroke conditions, and therefore, oxidative stress can be still a viable target for acute stroke therapy.